Adverse Events After SARS-CoV-2 mRNA Vaccination Among Patients With Inflammatory Bowel Disease. (21st August 2021) - Botwin, Gregory J.; Li, Dalin; Figueiredo, Jane; Cheng, Susan; Braun, Jonathan; McGovern, Dermot P. B.; Melmed, Gil Y.
Abstract : INTRODUCTION: Patients with immune-mediated inflammatory diseases such as inflammatory bowel disease (IBD) on immunosuppressive and biologic therapies were largely excluded from severe acute respiratory syndrome coronavirus-2 messenger RNA vaccine trials. METHODS: We evaluated adverse events (AE) after messenger RNA vaccination in 246 adults with IBD participating in a longitudinal vaccine registry. RESULTS: In general, AE frequency was similar to that reported in the general population. AEs were more common among younger patients and those with previous COVID-19. AEs were less common in individuals receiving advanced therapies with biologics or small-molecule inhibitors. DISCUSSION: Those with IBD and other immune-mediated inflammatory diseases can be reassured that the AE risk is likely not increased, and may be reduced, while on advanced therapies.